Mapping of Engineering Research Trend in Karnataka: A Special Reference to Visvesvaraya Technological University - Mulla, K.R.; Konnur, P.V. (DESIDOC Journal of Library & Information Technology, 2013)
This paper reports the analysis of doctoral dissertations awarded by Visvesvaraya TechnologicalUniversity (VTU). The primary objective of this study is to understand the growth and developmentof research activities of VTU in the past 13 years. The data for the present study has been collectedfrom two authenticated sources: (a) the data published in the University News: a weekly journal fromthe Association of Indian Universities and (b) the VTU website (http://www.vtu.ac.in/). There are 250doctoral degrees awarded from 2007 to 2011, in 14 engineering and allied domains. The data relatingto research growth and development were analysed and presented under 9 heads viz., chronological,department-wise, frequency-wise, rank-wise distributed doctoral dissertations, productivity of supervisors,ranking of research supervisors, and rank wise distribution of research centers. The authors analysed thebibliographic details of doctoral degrees awarded by VTU. The present situation is that, on an average 50doctoral degrees are being awarded in a year. In 2010 and 2011 the research output traced signifi cantgrowth with the awarding of 156 (62.40 %) doctoral degrees. Substantial research was carried out inmechanical (40.40 %) engineering department. It was also observed that 169 research supervisors arepresently engaged in guiding doctoral students. http://dx.doi.org/10.14429/djlit.33.1.3730